THE INVOLVEMENT OF PARENTS IN CHILDRENS’ LEARNING ENGLISH AT KARTIKA KINDERGARTEN OF JEMBER - Eniek Yuniarti (Universitas Muhammadiyah Gresik, 2016)
Parental involvement takes many forms including good parenting in the home, including the provision of a secure and stable environment, intellectual stimulation, parent-child discussion, good models of constructive social and educational values and high aspirations relating to personal fulfillment and good citizenship; contact with schools to share information; participation in school events; participation in the work of the school; and participation in school governance. The extent and form of parental involvement is strongly influenced. Parents involvements in education is really significant expected role,especially in the kindergarten level. It is because parents is the first place to explore their children creativity, thinking and their ability. Parental involvement is strongly positively influenced by the child’s level of attainment: the higher the level of attainment, the more parents get involved. The importance of parental involvements are used not only to get the best achievement in the school but also to help their children in their future life. The aim of this paper is to give a clear description of the involvement of parents in children’s’ learning English.